Self‐Assembled Microribbons: Light‐Driven Continuous Twist Movements of Microribbons (Small 7/2019). Issue 7 (15th February 2019) - Zhang, Yifan; Gong, Yanjun; Li, Bo; Ma, Ren‐Min; Che, Yanke; Zhao, Jincai
Abstract : In article number1804102, Ren‐Min Ma, Yanke Che, and co‐workers report a continuous twist movement of microribbons driven by scanning laser irradiation. Key factors in the achievement of this continuous movement are the fabrication of elastic microribbons that possess relatively low elastic modulus and diagonal photoinduced π‐stacking distortion relative to the microribbon long axis.